Public speaking anxiety and individual factors among undergraduate medical students at a public university in Malaysia - Mansor, Zawiah; Mohd Yunus, Nuraina Shahirah; Fong, Yan Bin; Venugopal, Vishnu (Universiti Putra Malaysia, 2024)
Introduction: Public speaking skills are crucial skills for medical students, enabling effective communication in their academic and future professional roles. However, public speaking anxiety (PSA) can hinder their full potential and warrant early intervention. This study aims to determine the prevalence of PSA and associated factors among medical undergraduates at a Malaysian public university. Materials and Methods: A cross-sectional study was conducted using a validated and reliable online self-administered questionnaire. The Personal Report of Public Speaking Anxiety (PRPSA) questionnaire was used to assess PSA level and other factors such as sociodemographic, English proficiency level, public speaking training and experience, and the CompACT questionnaire for psychological flexibility. Descriptive, bivariate, and multivariate analyses were performed. Result : The analysis included a total of 362 respondents. The prevalence of moderate and high PSA was 49.3%. There was a significant association between race, psychological flexibility, public speaking experience, public speaking training, and PSA (p<0.05). Multiple logistic regression analysis showed that having high to moderate PSA was significantly linked to being 19–21 years old (AOR: 1.70, 95% CI: 1.081-2.678) and never having had public speaking training (AOR: 1.865, 95% CI: 1.067–3.261). On the other hand, being more psychologically flexible was a protective factor (AOR: 0.944, 95% CI: 0.925–0.964). Conclusion: The high prevalence of PSA among medical students highlights the need for early recognition, screening, and intervention within the education system. Incorporating public speaking training and interventions to enhance psychological flexibility within the curriculum can be beneficial to prevent PSA for better-quality graduates.